Growth under external restrictions: empirical evidence for low-income countries in the context of the boom in international commodity prices (2000-2014) - Batista, Henrique Rogê (Brazilian Keynesian Review, 2021)
The present work is supported by post-Keynesian literature, applying the Thirlwall Multisectoral Law (2007), to test, in a sample of 19 low-income countries, whether balance of payments restricts the growth of the aggregated sample. The period selected for analysis aims to capture the boom in international commodity prices, which, given the composition of the exporting tariff by technological intensity of these countries, mainly primary products and with low technological intensity, tends to benefit their trading terms. In addition to the validity of the tested law, the results indicate that gains from rising commodity prices are diluted given the volume imported into the most technologically intensive and, even, commodity sectors.